Aflati y din {2 x [14 + (5 + y) : 6] - 5} : 9 + 7=10
Răspunsuri la întrebare
Răspuns de
0
{2*[14+(5+y):6]-5}:9=10-7=3
2*[14+(5+y):6]-5=3*9=27
2*[14+(5+y):6]=27+5=32
14+(5+y):6=32:2=16
(5+y):6=16-14=2
5+y=2*6=12
y=12-5
y=7
2*[14+(5+y):6]-5=3*9=27
2*[14+(5+y):6]=27+5=32
14+(5+y):6=32:2=16
(5+y):6=16-14=2
5+y=2*6=12
y=12-5
y=7
Alte întrebări interesante
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă